Evaluating the Impact of Training Program on Raising Productivity Efficiency at Najran University from the Staff Viewpoint (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aimed to evaluate the impact of training programs on raising the employee’s productive efficiency at Najran University from the Staff viewpoint. The sample included all active staff at Najran University. The study relied on a comprehensive survey method. An electronic questionnaire was distributed collecting data from the respondents. The study findings showed that the training sessions provided by the Skills Development Unit in the Deanship of Development and Quality are appropriate in terms of time and content, and that the training sessions are effective in terms of contribution. Raising the productive efficiency of faculty members and supporting staff, and that the results of training programs have a clear impact on raising the productive efficiency of the staff. The study recommended the need to strengthen the role of staff members and supporting staff at Najran University and their participation in identifying training needs and building future training strategies.
Keywords: Training Programs; Productive Efficiency; Impact Evaluation; Najran University